Thermoregulation and fluid balance during professional soccer competition in the heat - Aragón Vargas, Luis Fernando (2005)
Purpose: To evaluate initial hydration status, fluid balance, and core temperature changes during a regular season soccer game of the Costa Rica professional league. Methods: 18 starting male professional players (nine from each team, including both goalies) gave written informed consent to participate. Data were collected between 10.00 and 13.00h (approximately); the game started at 11.00h. Average environmental conditions were 34.9°C and 35.4% rh, for a WBGT heat stress index of 31.9°C. Upon arrival at the stadium, urine samples were collected and players were weighed nude. Fluid intake was monitored and urine production was collected from this point until players were weighed nude after the game. Core temperature (Tcore) was obtained before the game, at halftime, and at the end from disposable temperature sensors swallowed by the players 3 hours prior to the game. Data are mean±SD (range). Results: Initial urine specific gravity (USG) was 1.018±0.008 (1.003–1.036); seven players showed USG ≥ 1.020. Body mass (BM) loss was 2.58±0.88kg (1.08–4.17kg), equivalent to a dehydration of 3.38±1.11%BM (1.68–5.34%BM). Sweat loss was 4448±1216mL (2950–6224mL), while fluid intake totalled 1948±954mL (655–4288mL); only 82±119mL (0–512mL) of urine were collected. Tcore ≥ 39.0°C was registered in four players by halftime, in nine by game end. Conclusions: In spite of reasonably high fluid intakes, these players incurred significant dehydration during the game and thermoregulation was impaired. The problem was worse because several players arrived already dehydrated. To protect the physical integrity of the players, soccer competition should not be scheduled in these environmental conditions. Supported by the Gatorade Sports Science Institute and UCR-VI-245-A4-303.